Elite female gymnasts at two Olympic Games - quality or luck? - Delaš Kalinski, S. (Science of Gymnastics Journal, 2017)
Relatively small number of gymnasts participate at the Olympic Games and even smaller number participates at Olympic Games consecutively, due to numerous different reasons. Therefore, this paper aims are: 1) to determine the number of female gymnasts who participated in the C-I competition at Olympic Games held in 2012 and at Olympic Games held in 2016; 2) to determine characteristics and differences in results of consecutive participants at these two Olympic Games; 3) to determine differences between consecutive participants and other competitors at the afore defined competitions. It was found that 25 female gymnasts participated at two consecutive Olympic Games. From one to another Olympic Games, consecutive participants have numerically increase all scores; significantly increased Execution and Final Scores on the uneven bars; significantly decrease Execution and Final Score on the balance beam. Compared to other gymnasts from the 2012 and 2016 Olympic Games, consecutive participants had numerically higher values in all variables, but only some of them have been determined as significantly different. Consecutive participants confirmed the possibility of continuous quality of skills development in mid 20s.